2020
DOI: 10.1111/cen.14251
|View full text |Cite
|
Sign up to set email alerts
|

Open vs laparoscopic adrenalectomy for localized adrenocortical carcinoma

Abstract: Objective The purpose of the study was to compare the long‐term outcomes of patients with localized adrenocortical carcinoma (ACC) subjected to open vs laparoscopic surgery. Design Retrospective study. Patients This retrospective study included 46 patients with the ACC ENSAT stage I‐stage III of whom 23 underwent open surgery (OA group), whereas 23 were subjected to laparoscopic adrenalectomy (LA group). The main outcomes analysed in the study were differences between the OA and LA groups in recurrence‐free su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Patients treated with open adrenalectomy (OA) were more likely to have a larger tumor: median size was from 6.8 to 14 cm for ACC treated by OA, and from 5.5 to 9 cm for tumors treated by mini-invasive surgery. Seven studies showed that LA was effective for ACC when the tumor size is <10 cm and showed no local invasion, enlarged lymph-nodes or distant metastases (ENSAT stage I–II) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Some authors suggested that LA should be only performed in high volume referral centers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients treated with open adrenalectomy (OA) were more likely to have a larger tumor: median size was from 6.8 to 14 cm for ACC treated by OA, and from 5.5 to 9 cm for tumors treated by mini-invasive surgery. Seven studies showed that LA was effective for ACC when the tumor size is <10 cm and showed no local invasion, enlarged lymph-nodes or distant metastases (ENSAT stage I–II) [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Some authors suggested that LA should be only performed in high volume referral centers.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggested that LA should be only performed in high volume referral centers. Twelve studies reported a total of 89 conversions from MIS to an open approach [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Conversely, eight further studies [ 38 , 46 , 47 , 49 , 50 , 51 , 52 , 53 ] confirmed OA as the standard operative technique for ACC.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the ENSAT stage system, three studies included stage I-II patients [ 6 , 7 , 8 ]; six studies included stage I-III patients [ 9 , 10 , 11 , 12 , 13 , 14 ], and five studies included stage I-IV patients [ 15 , 16 , 17 , 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Notwithstanding, several authors suggested favorable oncological outcomes of MIA for ACC [ 6 , 7 , 14 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various factors may contribute to a more favorable ACC treatment outcome in expert centers. Center volume and surgical experience are crucial in this regard [18,19], but other factors, such as optimal post-surgical care, including a standardized follow-up protocol by a multidisciplinary team of experts and adjuvant mitotane treatment, could also play an important role. In the present study, the majority of the patients operated in the LVCs were referred to the HVC within three months after the surgery, and they were subjected to identical follow-up monitoring and treatment protocol as the patients operated on in the HVC.…”
Section: Discussionmentioning
confidence: 99%